2020
DOI: 10.1192/j.eurpsy.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Familial and socioeconomic contributions to premorbid functioning in psychosis: Impact on age at onset and treatment response

Abstract: Background. Premorbid adjustment (PA) abnormalities in psychotic disorders are associated with an earlier age at onset (AAO) and unfavorable clinical outcomes, including treatment resistance. Prior family studies suggest that familial liability, likely reflecting increased genetic risk, and socioeconomic status (SES) contribute to premorbid maladjustment. However, their joint effect possibly indicating gene–environment interaction has not been evaluated. Methods. We examined whether fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 81 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…In this research, the only characteristic that was shown to improve insight was a low BMI. The amount of baseline insight was strongly related to premorbid IQ (Molina-García et al, 2021;Gavett, Ashendorf and O'Bryant, 2022) (Hatzimanolis et al, 2020). Other research discovered other characteristics connected with insight (cognitive functionsmemory and executive functions), psychiatric and addiction comorbidities, associated personality disorders prescription psychotropic medicines, social cognitions, and psychotherapy usage.…”
Section: Understanding Of Eating Disordersmentioning
confidence: 96%
“…In this research, the only characteristic that was shown to improve insight was a low BMI. The amount of baseline insight was strongly related to premorbid IQ (Molina-García et al, 2021;Gavett, Ashendorf and O'Bryant, 2022) (Hatzimanolis et al, 2020). Other research discovered other characteristics connected with insight (cognitive functionsmemory and executive functions), psychiatric and addiction comorbidities, associated personality disorders prescription psychotropic medicines, social cognitions, and psychotherapy usage.…”
Section: Understanding Of Eating Disordersmentioning
confidence: 96%
“…In considering premorbid courses of development, individuals with schizophrenia on average demonstrate increasing impairments in social activity and consistently poorer academic and occupational functioning up to 15 years before first hospitalization (Velthorst et al, 2016). In literature dating back to at least 1969, individuals with schizophrenia with higher levels of premorbid functioning generally demonstrate better treatment response to pharmacological interventions compared to individuals with lower levels of premorbid functioning (Goldstein, Judd, Rodnick, & LaPolla, 1969; Hatzimanolis et al, 2020; Klein & Rosen, 1973; Rabinowitz et al, 2011; Strous et al, 2004). Similarly, overall premorbid functioning has been shown to positively predict overall cognitive remediation outcomes (Buonocore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[16] Some medical treatments need greater radiation doses, which are defined by several metrics on patient dosages [17]- [20]. The use of Dosimetry by the personnel has aided in estimating the degree of exposure [21]- [23]. A high clinical radiation exposure to the patient mostly during operations in a previous investigation.…”
Section: Introductionmentioning
confidence: 99%